Rancang Bangun Sistem Informasi Sikoba Berbasis Web Untuk Pengelolaan Kontrak Dan Bast Di BPS Kota Sukabumi - Muhammad Sheva Adyaksa Rohendi; Setiawati (Jurnal Sains Informatika Terapan, 2026)
This research aims to design and build a web-based Contract and Minutes Application (SIKOBA) system to support the Contract and Minutes of Handover (BAST) process at the BPS of Sukabumi City. Previously, this data management was still done manually, which complicated the monitoring process, information retrieval, and increased the risk of recording errors. The system was developed using Next.js and TypeScript on the frontend, Express.js on the backend, and PostgreSQL as the database. The development method used a prototype approach, where the system was built in stages and refined based on user input. The system implements role-based authentication that differentiates admin and user access rights. Admins are responsible for managing master data and monitoring documents, while users create contracts and BAST. The development results show that the system is able to improve data management efficiency, accelerate document creation processes, and support the digitalization of administration within the BPS of Sukabumi City.